Sejarah Tradisi Tulis Dalam Masyarakat Sasak Lombok - Jamaluddin Jamaluddin (Ulumuna, 2005)
A great number of classical intellectual treatises, usually called manuscripts, can be found in Lombok, an island in West Nusa Tenggara province. All the manuscripts indicate that writing tradition has been growing in this island since a long time ago. Of many factors influenced the growing of that tradition is trade relationship between Lombok traders and those from other islands. Some significant contributions can be traced through languages ever used in oral communication and in works produced in the community i.e. Sasak, Java, Bali, and Malay, Sanskrit, Arabics. The relationship also contributed to rising intellectual activity and enriching contents of the manuscripts. This article observes historical sides of the writing tradition by providing historical data, epigraphs and other supporting resources that made the writing tradition exist. The article tradition in Sasak community is predicted to have been started since the Sasak people recognized writing system, and have developed hundreds of years ago, producing thousands of manuscripts in some different languages, titles and forms.The writing systems used were varied such as old Javanese, Arab, Bali and Bugis. And the languages used were old Java, Java, Bali, Arabic and Malay. This indicates that, long time ago, Sasak people had made contact with people from many parts of this archipelago like Bali, Java, Malay and even Celebes (Bugis).